2021
DOI: 10.48550/arxiv.2110.11947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replica Wormholes and Holographic Entanglement Negativity

Xi Dong,
Sean McBride,
Wayne W. Weng

Abstract: Recent work has shown how to understand the Page curve of an evaporating black hole from replica wormholes. However, more detailed information about the structure of its quantum state is needed to fully understand the dynamics of black hole evaporation. Here we study entanglement negativity, an important measure of quantum entanglement in mixed states, in a couple of toy models of evaporating black holes. We find four phases dominated by different types of geometries: the disconnected, cyclically connected, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
(43 reference statements)
3
20
0
Order By: Relevance
“…Because there is no common geodesic element between all three elements (that is Γ(g A , e) ∩ Γ(g B , e) ∩ Γ(g A , g B ) is empty), there is no simple argument that determines the phase in this region. 7 This is the main difference between our calculation and the negativity computations in [26,33,34]. Instead we must seek other methods for determining the phase in this region.…”
Section: Phase Diagram and Rényi Reflected Entropiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there is no common geodesic element between all three elements (that is Γ(g A , e) ∩ Γ(g B , e) ∩ Γ(g A , g B ) is empty), there is no simple argument that determines the phase in this region. 7 This is the main difference between our calculation and the negativity computations in [26,33,34]. Instead we must seek other methods for determining the phase in this region.…”
Section: Phase Diagram and Rényi Reflected Entropiesmentioning
confidence: 99%
“…It was recently applied to find the entanglement entropy of JT gravity [25] and generic fixed area states [24]. Similar techniques were used to calculate the negativity [33,48]. This powerful approach enables us to write down the Schwinger-Dyson equation for the resolvent of ρ AB , which then gives full information about the entanglement spectrum.…”
Section: Schwinger-dyson For Entanglement Entropymentioning
confidence: 99%
“…It would be interesting to generalize this formalism to non-Abelian symmetry groups and systems with local symmetry constraints such as in the gauge theories and anyon chains [114] and possibly pinpoint the differences. Recently, the entanglement negativity of random tensor networks [22,23,26] was investigated. Given the dramatic effects of global symmetries on entanglement properties of single tensors (which was studied in the current work), it may be worth exploring which universal properties in random tensor networks would change in the presence of global symmetries.…”
Section: Discussionmentioning
confidence: 99%
“…[11] was introduced and employed to calculate the entanglement negativity and the entanglement negativity spectrum in the setting outlined above (see also Refs. [22][23][24][25][26] for a similar diagrammatic approach to the entanglement negativity and relative entropy of random tensor networks and models of evaporating black holes); it was shown that the main parameter controlling the entanglement behavior is q = L B L A , where L s denotes the Hilbert space dimension of s = A, B. Looking at extreme limits of this parameter is illuminating: for q 1 one expects the bath to be very large and thus A to be almost fully entangled with B resulting in a minimal entanglement between A 1 and A 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The technique we use here was presented in Ref. [5] (see also [23][24][25]). This powerful approach enables us to write down a Schwinger-Dyson equation for the resolvent of ρ R 1 R 2 , which then gives full information about the entanglement spectrum.…”
Section: Resolvent Trickmentioning
confidence: 99%